Suspect communities: anti-Muslim racism and the domestic war on terror - Nguyen, Nicole (University of Minnesota Press, 2019)
Introduction: defining the enemy within -- Ethnographic dilemmas : rethinking power relations when studying up -- Left of boom : remaking the global war on terror -- "The R word" : radicalization theories and their discontents -- Patriot acts : managing public objections to CVE -- The generational threat : youth radicalization and the domestic war on terror -- Conclusion: reimagining national security -- Appendix -- Notes -- Bibliography -- Index.